Being-in-America: white supremacy and the American self - Richardson, Ronald Kent (Peter Lang, 2024)
"White supremacy and American style individual autonomy are mutually supportive and co-dependent. Attacking white racism will not dislodge white supremacy, which the author contends is the greatest danger facing America. That can only be accomplished by making concurrent and significant modifications in American style individualism. Yet, white supremacist thinking, feeling and acting and American individualism are protected by what the author describes as The White Supremacist Collective Unconscious, a culturally determined mental construct that Americans assimilate as they grow into adulthood, which endows all Americans, regardless of race, with a white supremacist mental orientation to one degree or another. Drawing on his personal experiences as an African American growing up in the United States, and on his research, the author details the development and workings of that unconscious, and the impact of white supremacy on the national character"--